Electronic device or regulated tobacco product? Learning from the diffusion of heated tobacco products in Spain - Martín-Álvarez, Juan Manuel; Almeida, Alejandro; Golpe, Antonio A.; Asensio, Eva (Public Health, 2023)
Objectives: Tobacco companies have introduced heated tobacco product (HTP) in many countries and marketed it on the grounds that it is a less harmful alternative to health. However, tobacco companies have been widely criticized for taking advantage of a loophole that allows electronic devices to circumvent regulations limiting tobacco advertising. This work aims to determine whether HTPs respected the rules that regulate tobacco advertising when it was introduced in Spain. Study design: This is an observational epidemiological study. Methods: Using monthly time series data from September 2016 to June 2020, we analyzed whether the adoption of HTPs has followed the same behavior patterns as other brands that were introduced under the same conditions of use. The Bass model is used to analyze the diffusion of HTPs, and 30 other traditional cigarette brands introduced under the same conditions as this HTPs. Results: The adoption of HTPs in Spain has been like that of brands of slim cigarettes that are mistakenly considered to be healthier than traditional cigarettes. The results indicate that the use of HTPs has spread in the same way as additive-free and ultra-slim cigarette brands. Conclusions: Policymakers should keep in mind that laws should restrict any marketing of tobacco products that promotes positive connotations between tobacco use and being healthy. If manufacturers are allowed to classify a category and/or brand of tobacco products as less harmful to health, the imitation effect is very high, leading to the proliferation of smoking.
Keywords: electronic nicotine delivery devices; tobacco marketing; Scopus